2004
DOI: 10.1074/jbc.m407410200
|View full text |Cite
|
Sign up to set email alerts
|

Clioquinol Mediates Copper Uptake and Counteracts Copper Efflux Activities of the Amyloid Precursor Protein of Alzheimer's Disease

Abstract: The key protein in Alzheimer's disease, the amyloid precursor protein (APP), is a ubiquitously expressed copper-binding glycoprotein that gives rise to the A␤ amyloid peptide. Whereas overexpression of APP results in significantly reduced brain copper levels in three different lines of transgenic mice, knock-out animals revealed increased copper levels. A provoked rise in peripheral levels of copper reduced concentrations of soluble amyloid peptides and resulted in fewer pathogenic A␤ plaques. Contradictory ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 33 publications
3
127
0
1
Order By: Relevance
“…A phase III clinical trial termed PBT2 (see http:// www.alzforum.org/drg/drc/detail.asp?ids110) is under way. However, even if clioquinol turns out to counteract AD, it might not act by merely scavenging copper, but rather to function as a copper carrier to effectively increase intracellular copper levels, as was shown in a yeast model (Treiber et al, 2004). Thus, while elevated zinc levels promote Ab aggregation and have adverse effects in vivo, the role of copper remains to be elucidated.…”
Section: Figurementioning
confidence: 99%
“…A phase III clinical trial termed PBT2 (see http:// www.alzforum.org/drg/drc/detail.asp?ids110) is under way. However, even if clioquinol turns out to counteract AD, it might not act by merely scavenging copper, but rather to function as a copper carrier to effectively increase intracellular copper levels, as was shown in a yeast model (Treiber et al, 2004). Thus, while elevated zinc levels promote Ab aggregation and have adverse effects in vivo, the role of copper remains to be elucidated.…”
Section: Figurementioning
confidence: 99%
“…Clioquinol has a moderate affinity for iron, copper, and zinc (Kd Cu is 1.2×10 -10 M, Kd Zn is 7×10 -8 M) [197], and for this reason it was explored as a drug for AD. Although it was initially considered a chelator [198][199][200][201], it has more recently been characterized as a copper/zinc ionophore, which functions to redistribute these metals into cells [196,[202][203][204][205][206]. Clioquinol is still considered a moderate iron chelator as it has been shown to lower iron levels in animal models of iron overload [64,148,[207][208][209][210], and has not been shown to redistribute iron into cells using ionophore assays.…”
Section: Clioquinol and Pbt2mentioning
confidence: 99%
“…However, studies to ascertain whether chelators might function in this regard revealed a complex interplay of effects on metal ion homeostasis. Thus, in the case of clioquinol, a drug that underwent initial clinical trials for treatment of AD, benefits appear to arise from counteracting the intracellular copper-depleting effects of A PP (157).…”
Section: Role Of Oxidative Stress In Admentioning
confidence: 99%